Pelvic symptoms after radiotherapy in prostate cancer: a cross-sectional study - Aline Moreira Ribeiro; Fernanda Maris Peria; Elaine Cristine Lemes Mateus-Vasconcelos; Cristine Homsi Jorge Ferreira; Valdair Francisco Muglia; Harley Francisco de Oliveira
Abstract Introduction: Despite the technical and scientific progress that improved therapeutic resources available in Oncology, adverse effects of treatment can be prominent, impacting the quality of life (QoL). Objective: This research aims to determine the prevalence of post-radiotherapy pelvic symptoms in prostate cancer (PC) and its impact on QoL. Methods: We assessed three groups of patients at different stages during radiotherapy (RT): Pre-RT, evaluated before of RT; Post-RT#1, evaluated between six months and one year post-RT; Post-RT#2, evaluated between two and a half and four years post-RT. The presence of urinary incontinence (UI), its characteristics and impact on daily living activities (DLA) were evaluated by ICIQ-SF questionnaire. WHOQOL-BREF questionnaire was used to assess QoL. Student t test was used, considering significant p < 0.05. Results: Thirty-three men were assessed (pre-RT, n = 12; Post-RT#1, n = 10; Post-RT#2, n = 11). The prevalence of lower urinary tract symptoms (LUTS) was highest in Post-RT#1 group. Post-RT#2 group had the highest prevalence of post-RT UI. In QoL, Pre-RT and Post-RT#2 groups experiencing the greatest impact on physical, environmental and overall QoL. Conclusion: Acute effect of RT is characterized by a high prevalence of LUTS. Post-RT#2 group experienced the most adverse effects on DLA due to a higher prevalence of post-RT UI.